Enhanced Antifungal Efficacy of Validamycin A Co-Administered with Bacillus velezensis TCS001 against Camellia anthracnose - Zhilei Chen; Hao Cao; Jing Jin; Zhong Li; Shouke Zhang; Jie Chen (Plants, 2024)
Anthracnose, a fungal disease harming fruit trees and crops, poses a threat to agriculture. Traditional chemical pesticides face issues like environmental pollution and resistance. A strategy combining low-toxicity chemicals with biopesticides is proposed to enhance disease control while reducing chemical use. Our study found that mixing validamycin A (VMA) and Bacillus velezensis TCS001 effectively controlled anthracnose in Camellia oleifera. The combination increased antifungal efficacy by 65.62% over VMA alone and 18.83% over TCS001 alone. It caused pathogen deformities and loss of pathogenicity. Transcriptomic analysis revealed that the mix affected the pathogen’s metabolism and redox processes, particularly impacting cellular membrane functions and inducing apoptosis via glycolysis/gluconeogenesis. In vivo tests showed the treatment activated C. oleifera’s disease resistance, with a 161.72% increase in polyphenol oxidase concentration in treated plants. This research offers insights into VMA and TCS001’s mechanisms against anthracnose, supporting sustainable forestry and national edible oil security.